Homosocial spaces in the Carnival of Barranquilla: between the literary chronicle and the autobiographical novel - González Cueto, Danny Armando (2017)
Our research is about the homosocial spaces generated by the Carnival of Barranquilla, in which subjects MsM, known as "cigarrones"", maintain intimate relationships with homosexuals. That behaviour is tolerated during the days of celebration, although it is not usually part of the culture of the Region, as shown by some literary works such El cadaver de papá (1978) or Maricones Eminentes (1999) by Jaime Manrique Ardila and Locas de felicidad (2009) by John Better. How has this peculiar reality been represented into the literary medium? What characteristics make this representation? What evolution have they had across time?"